High Estimated Glomerular Filtration Rate Is Associated With Worse Cognitive Performance in the Hypertensive Population: Results From the China H-Type Hypertension Registry Study - Li, Junpei; Yu, Shichao; Tan, Ziheng; Yu, Yun; Luo, Linfei; Zhou, Wei; Zhu, Linjuan; Wang, Tao; Cao, Tianyu; Tu, Jianglong; Bao, Huihui; Huang, Xiao; et al. (Frontiers in Aging Neuroscience, 2022)
Background Increasing studies have focused on the predictive value of high estimated glomerular filtration rate (eGFR) on cardiovascular diseases and mortality; however, the association between high eGFR with cognitive function is still not established. Thus, this study aimed to determine the co-relationship between high eGFR and cognitive performance in the hypertensive population. Methods We conducted a baseline cross-sectional study using data from the China H-type Hypertension Registry study. Mini-Mental State Examination (MMSE) assessment was performed to evaluate the cognitive function scale, and serum creatinine was collected to estimate eGFR level. Different MMSE cutoff values were applied in participants with the various educational background to define dementia: <24 in participants with secondary school and above education setting, <20 in those with primary school, and <17 in illiterate participants. Results A total of 9,527 hypertensive adults with mean age 63.7 ± 9.8 years and 67% female gender were analyzed. The eGFR cutoff value of 71.52 ml/min/1.73 m2 was found after adjusting for potential covariates in a threshold effect analysis. The MMSE increased significantly with the increment of eGFR (β, 0.27; 95% CI: 0.12–0.41) in participants with eGFR < 71.52 ml/min/1.73 m2 and decreased (β, −0.28; 95% CI: −0.39 to −0.17) in participants with eGFR ≥ 71.52 ml/min/1.73 m2. Individuals with eGFR ≥ 85 ml/min/1.73 m2 have an elevated risk of cognitive impairment than those with eGFR of 65–75 ml/min/1.73 m2. Subgroup analysis showed that a greater reduction degree of MMSE was observed in female individuals and those who had body mass index (BMI) ≥ 24 kg/m2 among participants with eGFR ≥ 71.52 ml/min/1.73 m2. Conclusion Our findings observed an inverted U-shaped relationship between eGFR and cognitive function. Both the low and high levels of eGFR were independently associated with worse cognitive assessment in the hypertensive population.